1990
DOI: 10.1530/acta.0.1230613
|View full text |Cite
|
Sign up to set email alerts
|

Effects of methimazole treatment on growth hormone (GH) response to GH-releasing hormone in patients with hyperthyroidism

Abstract: Abstract. In vitro studies have demonstrated that thyroid hormones can enhance basal and stimulated growth hormone secretion by cultured pituitary cells. However, both in man and in the rat the effects of high thyroid hormone levels on GH secretion are unclear. The aim of our study was to test the GH response to human GHRH in hyperthyroid patients and to evaluate the effects on GH secretion of short- and long-term pharmacological decrease of circulating thyroid hormones. We examined 10 hyperthyroid patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
22
2

Year Published

1991
1991
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 0 publications
5
22
2
Order By: Relevance
“…Our data confirm that hyperthyroid patients show blunted GH responses to GHRH [9]. The mechanism by which the elevation in the serum concentration of thy roid hormones inhibits GH secretion remains to be explained.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Our data confirm that hyperthyroid patients show blunted GH responses to GHRH [9]. The mechanism by which the elevation in the serum concentration of thy roid hormones inhibits GH secretion remains to be explained.…”
Section: Discussionsupporting
confidence: 81%
“…pretreating animals with thyroxine has been reported to decrease the GH response to GHRH as com pared to the euthyroid state [11], In man, several studies have reported that hyperthyroid patients have reduced spontaneous GH secretion (21) and that the GH re sponse to various stimuli, such as insulin-induced hypo glycemia [8,9] and p-adrenergic blockers [22,23] is impaired in hyperthyroidism. The GH response to GHRH in hyperthyroid patients has also been reported to be blunted [9,12]. a-Adrenergic pathways play an important role in reg ulating GH secretion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The hypothesis that arginine sup presses endogenous somatostatin release is also supported by the observation that arginine is able to enhance the TSH response toTRH in normal human subjects [14] and to normalize the GH response to GHRH in patients thought to have high somatostatin tone, e.g. under chronic glucocorticoid treatment [28], Our data confirm that hyperthyroid patients have blunted GH responses to GHRH [9], The mechanism by which the elevation in the serum concentration of thyroid hormones inhibits GH secretion remains to be explained. We have shown that, in hyperthyroid patients, pretreat ment with the P-blocker propranolol enhances the GH response to GHRH ( 1-29)NH: [29], On the basis of these results, it has been hypothesized that GH inhibition in hyperthyroid patients is mediated, at least in part, as in patients treated with glucocorticoids [30], by an increase in the hypothalamic secretion of somatostatin.…”
Section: Discussionsupporting
confidence: 76%
“…9] and p-adrenergic block ers [21,22], is impaired in hypertyroidism. The GH response to GHRH in hyperthyroid patients has also been reported to be blunted [9,12], Moreover, pharmacologi cal substances thought to stimulate endogenous GHRH secretion, such as clonidine [23] and galanin [24]. are not able to reverse GH inhibition in hyperthyroidism [25,26] Arginine is a well-known GH secretagogue [13].…”
Section: Discussionmentioning
confidence: 99%